A novel p38α MAPK inhibitor suppresses brain proinflammatory cytokine up-regulation and attenuates synaptic dysfunction and behavioral deficits in an Alzheimer's disease mouse model - Munoz, Lenka (BioMed Central, 2007)
BACKGROUND: An accumulating body of evidence is consistent with the hypothesis that excessive or prolonged increases in proinflammatory cytokine production by activated glia is a contributor to the progression of pathophysiology that is causally linked to synaptic dysfunction and hippocampal behavior deficits in neurodegenerative diseases such as Alzheimer's disease (AD). This raises the opportunity for the development of new classes of potentially disease-modifying therapeutics. A logical candidate CNS target is p38α MAPK, a well-established drug discovery molecular target for altering proinflammatory cytokine cascades in peripheral tissue disorders. Activated p38 MAPK is seen in human AD brain tissue and in AD-relevant animal models, and cell culture studies strongly implicate p38 MAPK in the increased production of proinflammatory cytokines by glia activated with human amyloid-beta (Aβ) and other disease-relevant stressors. However, the vast majority of small molecule drugs do not have sufficient penetrance of the blood-brain barrier to allow their use as in vivo research tools or as therapeutics for neurodegenerative disorders. The goal of this study was to test the hypothesis that brain p38α MAPK is a potential in vivo target for orally bioavailable, small molecules capable of suppressing excessive cytokine production by activated glia back towards homeostasis, allowing an improvement in neurologic outcomes. METHODS: A novel synthetic small molecule based on a molecular scaffold used previously was designed, synthesized, and subjected to analyses to demonstrate its potential in vivo bioavailability, metabolic stability, safety and brain uptake. Testing for in vivo efficacy used an AD-relevant mouse model. RESULTS: A novel, CNS-penetrant, non-toxic, orally bioavailable, small molecule inhibitor of p38α MAPK (MW01-2-069A-SRM) was developed. Oral administration of the compound at a low dose (2.5 mg/kg) resulted in attenuation of excessive proinflammatory cytokine production in the hippocampus back towards normal in the animal model. Animals with attenuated cytokine production had reductions in synaptic dysfunction and hippocampus-dependent behavioral deficits. CONCLUSION: The p38α MAPK pathway is quantitatively important in the Aβ-induced production of proinflammatory cytokines in hippocampus, and brain p38α MAPK is a viable molecular target for future development of potential disease-modifying therapeutics in AD and related neurodegenerative disorders.